Brown Adipose Tissue Is Linked to a Distinct Thermoregulatory Response to Mild Cold in People - Chondronikola, Maria; Volpi, Elena; Børsheim, Elisabet; Chao, Tony; Porter, Craig; Annamalai, Palam; Yfanti, Christina; Labbe, Sebastien M.; Hurren, Nicholas M.; Malagaris, Ioannis; Cesani, Fernardo; Sidossis, Labros S. (Frontiers in Physiology, 2016)
Brown adipose tissue (BAT) plays an important role in thermoregulation in rodents. Its role in temperature homeostasis in people is less studied. To this end, we recruited 18 men [8 individuals with no/minimal BAT activity (BAT-) and 10 with pronounced BAT activity (BAT+)]. Each volunteer participated in a 6 h, individualized, non-shivering cold exposure protocol. BAT was quantified using positron emission tomography/computed tomography. Body core and skin temperatures were measured using a telemetric pill and wireless thermistors, respectively. Core body temperature decreased during cold exposure in the BAT- group only (-0.34oC, 95% CI: -0.6 to -0.1, p = 0.03), while the cold-induced change in core temperature was significantly different between BAT+ and BAT- individuals (BAT+ vs. BAT-, 0.43oC, 95% CI: 0.20 to 0.65, p = 0.0014). BAT volume was associated with the cold-induced change in core temperature (p = 0.01) even after adjustment for age and adiposity. Compared to the BAT- group, BAT+ individuals tolerated a lower ambient temperature (BAT-: 20.6± 0.3oC vs. BAT+: 19.8 ± 0.3oC, p=0.035) without shivering. The cold-induced change in core temperature (r = 0.79, p = 0.001) and supraclavicular temperature (r = 0.58, p = 0.014) correlated with BAT volume, suggesting that these non-invasive measures can be potentially used as surrogate markers of BAT when other methods to detect BAT are not available or their use is not warranted. These results demonstrate a physiologically significant role for BAT in thermoregulation in people. This trial has been registered with Clinaltrials.gov: NCT01791114 https://clinicaltrials.gov/ct2/show/NCT01791114)